Why Was “Self-Government” Not Achieved in Aceh? The Challenges of Implementing a Peace Agreement - Zainal, Suadi; Askandar, Kamarulzaman; Abubakar, Muhammad bin (Jurnal Ilmiah Peuradeun, 2022)
The "self-government" was proposed as an alternative solution to independence and special autonomy to end the protracted conflict in Aceh. Based on the contents of the peace agreement signed in 2005, Aceh is given the right to self-government. However, this is not realized fully. This study aimed to explain the imagined self-government and the causes challenging it to be implemented. The study used a qualitative library research method in which data was sourced from online text documents. The data were analyzed using critical discourse analysis. The study found that the issue of "self-government" was initially at the center of the negotiation. The Free Aceh Movement - GAM envisioned it like Olan Island in Finland and Sarawak in Malaysia. Still, it has not been realized because it was not declared explicitly in the agreement, and the term "self-government" was used as a strategy to persuade GAM negotiators to continue in the negotiation. Further, the Government of Indonesia (GoI) offered Aceh special autonomy instead of self-government through the Law on Governing Aceh by ignoring the limitations on the authority of GoI over Aceh that was agreed. This was caused by five reasons that lay in the negotiation process and the realization of the agreement interconnected. Amongst; GAM was unbalanced to GoI during the negotiations and powerless to force GoI to obey the deal, and there was no punishment mechanism for the violator of the agreement. Finally, the study revealed that an inclusive process in drafting new laws for a post-conflict region does not always result in full outcomes by the agreement.